Resident Behaviours to Prioritize According to Canadian Plastic Surgeons. Issue 3 (August 2020) - Mankowski, Peter; Demsey, Daniel; Brown, Erin; Knox, Aaron
Introduction: Many articles have been published outlining the resident selection process for plastic surgery training programs. However, which qualities Canadian plastic surgeons value most in their current residents remains unclear. A national survey study was conducted to identify which attributes surgeons associate with the highest resident performance and which behaviours trainees should prioritize during their training. Methods: A literature review was performed to identify studies that documented attributes valued in plastic surgery applicants and characteristics of high-performing surgical residents. These qualities were extracted to construct a survey consisting of both ranking and open-ended questions. After an iterative review process, the survey was disseminated nationally to consultants and trainees of Canadian plastic surgery training programs. Results: Survey responses were obtained from 120 invitees and a weighted rank was calculated for each evaluated attribute. The terms integrity, professional, and work ethic were viewed as the most important attributes prized by surgeons. Dishonesty, lack of dependability, and unprofessionalism were viewed as the most concerning behaviours. Additionally, disinterest and arrogance were identified by the open-ended questions as behaviours surgeons would like to see less frequently in their trainees. When compared to surgeons, trainees undervalued the importance of knowledge and the impact of unprofessional behaviour. Conclusions: With the multiple roles that a resident must fulfill, understanding which attributes are of the most importance will help focus self-directed learning and development within residency programs. Ultimately, instilling the importance of integrity and professionalism is most highly valued by members of the Canadian plastic surgery community.